2010
DOI: 10.1186/1471-2229-10-97
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Arabidopsis defense responses against Spodoptera littoralisby CPK-mediated calcium signaling

Abstract: BackgroundPlant Ca2+ signals are involved in a wide array of intracellular signaling pathways after pest invasion. Ca2+-binding sensory proteins such as Ca2+-dependent protein kinases (CPKs) have been predicted to mediate the signaling following Ca2+ influx after insect herbivory. However, until now this prediction was not testable.ResultsTo investigate the roles CPKs play in a herbivore response-signaling pathway, we screened the characteristics of Arabidopsis CPK mutants damaged by a feeding generalist herbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 46 publications
(59 reference statements)
4
105
0
3
Order By: Relevance
“…35,141 Induction of H 2 O 2 has been studied in oat, wheat, barley and groundnut against D. noxia, R. padi, Schizaphis graminum Rond., H. armigera and S. litura. 4,5,132,139 Argandona et al 144 observed induction of H 2 O 2 in barley infested with S. graminum after 20 min of infestation, indicating that H 2 O 2 could be the beginning of a cascade of physiological and molecular events leading to production of further defensive components, and protection of plants from subsequent damage. ROS mediate the defensive gene activation and establish additional defenses by regulating the transcription and/or by interacting with other signal components like phosphorylation in plant systems in response to a variety of stresses.…”
Section: Future Outlookmentioning
confidence: 99%
See 3 more Smart Citations
“…35,141 Induction of H 2 O 2 has been studied in oat, wheat, barley and groundnut against D. noxia, R. padi, Schizaphis graminum Rond., H. armigera and S. litura. 4,5,132,139 Argandona et al 144 observed induction of H 2 O 2 in barley infested with S. graminum after 20 min of infestation, indicating that H 2 O 2 could be the beginning of a cascade of physiological and molecular events leading to production of further defensive components, and protection of plants from subsequent damage. ROS mediate the defensive gene activation and establish additional defenses by regulating the transcription and/or by interacting with other signal components like phosphorylation in plant systems in response to a variety of stresses.…”
Section: Future Outlookmentioning
confidence: 99%
“…35 Herbivore induced signals rapidly spread over the leaf and leads to a strong Ca 2+ -dependent transmembrane potential (Vm) depolarization in the damage zone, and is followed by a transient Vm hyperpolarization in the surrounding area, and a constant depolarization at distances greater than 6-7 mm. 35,139 Organelle and apoplastic fluid Ca 2+ concentration is generally higher (about 10 4 to 10 5 times) as compared with that in the cytosol (100 and 200 nM.). However, upon insect attack, the cytosolic Ca 2+ increases, which in turn activates the calcium-sensing proteins such as calmodulin, calmodulin-binding proteins, and calcium-dependent protein kinases (CDPKs) that promote the signaling events such as, phosphorylation and transcriptional change.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Plant defensins are antimicrobial proteins with eight conserved cysteines and four disulfide bridges. Defensins attack lepidopteran -amylases, causing feeding inhibition (Kanchiswamy et al, 2010;Rayapuram & Baldwin, 2008). Plant glucanases, chitinases, lectins and dehydrins are induced after attack by lepidopteran and coleopteran pests (Ralph et al, 2006).…”
Section: Typical Anti-insect Toxinsmentioning
confidence: 99%